Socioemotional assistive resource in psychology (Research, Society and Development, 2022)
Some children in language development may have language disorders and/or difficulty in verbal expression. The use of games in psychotherapeutic care for these children is essential for a better understanding and intervention, as it allows access to contents that generate anguish and that are difficult to elaborate. Assistive technologies comprise the development of resources that can provide inclusion and independence for people with disabilities. So, which instrument or game could be inserted to this demand for a psychological reception and support for the development of communication? The aim is the creation of a ludic-therapeutic game that addresses issues related to communication and socio-emotional issues, for better intervention and management in the context of child psychotherapy. The applied methodology is based on the Integrated Product Development Process (PRODIP) composed of three macrophases: project planning, informational project and conceptual project, and for this study, the first two stages were carried out. Project planning includes activities that aim to guide decisions and actions. In the informational project, we sought to identify users' needs and transform them into product requirements. For this, 22 questionnaires were answered by psychologists working with children. After gathering the requirements, they were valued on the Mudge diagram. Then, the Quality Function Deployment (QFD) was applied, relating the users' requirements with those of the project and generating the characteristics that should be prioritized. Based on the methodology applied, a broad and hierarchical view of the requirements for product development was possible.